2008
DOI: 10.1021/es072062w
|View full text |Cite
|
Sign up to set email alerts
|

VOC and Particulate Emissions from Commercial Cigarettes: Analysis of 2,5-DMF as an ETS Tracer

Abstract: Emissions of particulate matter (PM) and a broad suite of target volatile organic compounds (VOCs) in total, main-stream (MS) and side-stream (SS) smoke emissions are measured for six types of commercial cigarettes. The suitability of 2,5-dimethyl furan (DMF) as a tracer for environmental tobacco smoke (ETS) is investigated using laboratory results and a field study of 47 residences. Over 30 VOCs were characterized in cigarette smoke, including several that have not been reported previously. "regular tar", "lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 29 publications
(58 reference statements)
6
67
1
Order By: Relevance
“…The occurrence of myosmine, isonicoteine and nicotyrine together with nicotine in tobacco cigarette smoke has been reported in previous studies [24,25]. 2,5-dimethylfuran is another compound characteristic of tobacco cigarette smoke that has been proposed as a specific marker [25][26][27][28][29]. In the present study, this compound was present in the chromatogram of the tobacco cigarette smoke and absent in those of the e-cigarette smoke ( Fig.…”
Section: Smoke From Tobacco Cigarettes and E-cigarettessupporting
confidence: 83%
“…The occurrence of myosmine, isonicoteine and nicotyrine together with nicotine in tobacco cigarette smoke has been reported in previous studies [24,25]. 2,5-dimethylfuran is another compound characteristic of tobacco cigarette smoke that has been proposed as a specific marker [25][26][27][28][29]. In the present study, this compound was present in the chromatogram of the tobacco cigarette smoke and absent in those of the e-cigarette smoke ( Fig.…”
Section: Smoke From Tobacco Cigarettes and E-cigarettessupporting
confidence: 83%
“…2,5-dimethylfuran has the advantage of not being an endogenous substance and that it can only be introduced in the respiratory system from exogenous sources: smoking is practically the only realistic source of this contamination. Moreover, recent studies have shown that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 14 2,5-dimethylfuran emissions do not differ by cigarette type [30]. The results obtained in the present study show that this compound yields significant differences between smokers and non-smokers in all conditions evaluated (e.g., short-and long-exposure, light and heavy consumption).…”
Section: Combined Effectsmentioning
confidence: 93%
“…Toluene and xylenes were chosen because VOC emissions by cigarette smoke are usually dominated by benzene and these compounds [30]. 2,5-dimethylfuran was included as recent studies have showed its strong correlation with smoking status [22,[24][25][26][27][28].…”
Section: Breath Analysismentioning
confidence: 99%
“…Typical values of pollutants usually checked in IAQ audits and released by one cigaratte burning are given in Table 10, which summarizes information collected in (Charles et al, 2008;REHVA, 2004 (DIN 1946(DIN , 1994; -indoor air quality, according to European Standard CEN 1752, described below. Ventilation efficiency ε v is a criterion for energy and fan performances.…”
Section: Metabolic Co 2 Computationmentioning
confidence: 99%